29. THE PREVALENCE OF LIVER FIBROSIS AND EFFECTIVENESS OF KNOWLEDGE AND PRACTICE INTERVENTIONS IN MIDDLE–AGED MALE ALCOHOL USERS (Vietnam Journal of Community Medicine, 2024)
Objective: (1) To determine the prevalence of liver fibrosis in middle–aged men who consume alcohol; (2) To assess the effectiveness of knowledge and practice interventions in improving liver fibrosis in middle–aged male alcohol users.Subject and method: A cross–sectional descriptive study with an uncontrolled intervention was conducted on 513 middle–aged male alcohol users who came Military Hospital 121 for a routine health check-up from April 2022 to March 2023.Results: The prevalence of liver fibrosis was 29.3%. After the intervention, the rate of achieving general knowledge increased from 18.4% to 82.3%, achieving general practice increased from 4.8% to 98.6%, and achieving both knowledge and practice increased from 0.0% to 81.6%. The prevalence of liver fibrosis decreased to 73.5%, with a statistically significant difference (p
Keywords: liver fibrosis; middle-aged men; alcohol consumption; knowledge and practice interventions